Headache neuroimaging: A survey of current practice, barriers, and facilitators to optimal use. Issue 1 (18th January 2022) - Reynolds, Evan L.; Burke, James F.; Evans, Lacey; Syed, Faiz I.; Liao, Eric; Lobo, Remy; Cooper, Wade; Charleston, Larry; Callaghan, Brian C.
Abstract: Objective: The objective of this study was to understand current practice, clinician understanding, attitudes, barriers, and facilitators to optimal headache neuroimaging practices. Background: Headaches are common in adults, and neuroimaging for these patients is common, costly, and increasing. Although guidelines recommend against routine headache neuroimaging in low‐risk scenarios, guideline‐discordant neuroimaging is still frequently performed. Methods: We administered a 60‐item survey to headache clinicians at the Veterans Affairs health system to assess clinician understanding and attitudes on headache neuroimaging and to determine neuroimaging practice patterns for three scenarios describing hypothetical patients with headaches. Descriptive statistics were used to summarize responses, stratified by clinician type (physicians or advanced practice clinicians [APCs]) and specialty (neurology or primary care). Results: The survey was successfully completed by 431 of 1426 clinicians (30.2% response rate). Overall, 317 of 429 (73.9%) believed neuroimaging was overused for patients with headaches. However, clinicians would utilize neuroimaging a mean (SD) 30.9% (31.7) of the time in a low‐risk scenario without red flags, and a mean 67.1% (31.9) of the time in the presence of minor red flags. Clinicians had stronger beliefs in the potential benefits (268/429, 62.5%) of neuroimaging compared to harms (181/429, 42.2%) and more clinicians were bothered by harms stemming from the omission of neuroimaging (377/426, 88.5%) compared to commission (329/424, 77.6%). Additionally, APCs utilized neuroimaging more frequently than physicians and were more receptive to potential interventions to improve neuroimaging utilization. Conclusions: Although a majority of clinicians believed neuroimaging was overused for patients with headaches, many would utilize neuroimaging in low‐risk scenarios with a small probability of changing management. Future studies are needed to define the role of currently used red flags given their importance in neuroimaging decisions. Importantly, APCs may be an ideal target for future optimization efforts.